Cerebrospinal fluid exploratory proteomics and ketamine metabolite pharmacokinetics in human volunteers after ketamine infusion - Ruin Moaddel; Cristan A. Farmer; Mani Yavi; Bashkim Kadriu; Min Zhu; Jinshui Fan; Qinghua Chen; Elin Lehrmann; Giovanna Fantoni; Supriyo De; Caio H. Mazucanti; Elia E. Acevedo-Diaz; et al. (iScience, 2023)
Summary: Ketamine is a treatment for both refractory depression and chronic pain syndromes. In order to explore ketamine’s potential mechanism of action and whether ketamine or its metabolites cross the blood brain barrier, we examined the pharmacokinetics of ketamine and its metabolites—norketamine (NK), dehydronorketamine (DHNK), and hydroxynorketamines (HNKs)—in cerebrospinal fluid (CSF) and plasma, as well as in an exploratory proteomic analysis in the CSF of nine healthy volunteers who received ketamine intravenously (0.5 mg/kg IV). We found that ketamine, NK, and (2R,6R;2S,6S)-HNK readily crossed the blood brain barrier. Additionally, 354 proteins were altered in the CSF in at least two consecutive timepoints (p < 0.01). Proteins in the classes of tyrosine kinases, cellular adhesion molecules, and growth factors, including insulin, were most affected, suggesting an interplay of altered neurotransmission, neuroplasticity, neurogenesis, synaptogenesis, and neural network functions following ketamine administration.